A comparison of populations vaccinated in a public service and in a private hospital setting in the same area - Ieraci Roberto; Graziani Maria C; Pandolfi Elisabetta; Cavagni Giovanni; Tozzi Alberto E (BMC, 2008)
Abstract Background Improving immunisation rates in risk groups is one of the main objectives in vaccination strategies. However, achieving high vaccination rates in children with chronic conditions is difficult. Different types of vaccine providers may differently attract high risk children. Aim To describe the characteristics of two populations of children who attended a private and a public immunisation provider in the same area. Secondarily, to determine if prevalence of patients with underlying diseases by type of provider differs and to study if the choice of different providers influences timeliness in immunisation. Methods We performed a cross-sectional study on parents of children 2 - 36 months of age who attended a private hospital immunisation service or a public immunisation office serving the same metropolitan area of Rome, Italy. Data on personal characteristics and immunisation history were collected through a face to face interview with parents of vaccinees, and compared by type of provider. Prevalence of underlying conditions was compared in the two populations. Timeliness in immunisation and its determinants were analysed through a logistic regression model. Results A total of 202 parents of children 2-36 months of age were interviewed; 104 were in the public office, and 98 in the hospital practice. Children immunised in the hospital were more frequently firstborn female children, breast fed for a longer period, with a lower birthweight, and more frequently with a previous hospitalisation. The prevalence of high risk children immunised in the hospital was 9.2 vs 0% in the public service (P = 0.001). Immunisation delay for due vaccines was higher in the hospital practice than in the public service (DTP, polio, HBV, and Hib: 39.8% vs 22.1%; P = 0.005). Anyway multivariate analyses did not reveal differences in timeliness between the public and private hospital settings. Conclusion Children with underlying diseases or a low birthweight were more frequently immunised in the hospital. This finding suggests that offering immunisations in a hospital setting may facilitate vaccination uptake in high risk groups. An integration between public and hospital practices and an effort to improve communication on vaccines to parents, may significantly increase immunisation rates in high risk groups and in the general population, and prevent immunisation delays.